The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/archdischild-2016-310955
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal ventilation with a manikin model and two novel PEEP valves without an external gas source

Abstract: PEEP between 4 cm HO and 5 cm HO was achieved when ventilating a neonatal manikin using a self-inflating bag and novel PEEP valves. Valves that can generate PEEP without external gas sources may aid resuscitation in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
8
1
Order By: Relevance
“…We did not record the respiratory system compliance in this experiment but expect it was within the range of 0.2–0.3 mL/kg/cmH 2 O, as shown previously 39. Compliance affects PEEP delivery: Tracy et al 18 tested 0.5 and 3 mL/cmH 2 O, and Thallinger et al 21 tested 0.1–0.2 and 0.8 mL/cmH 2 O. At a set PEEP of 5 cmH 2 O, both studies showed better PEEP provision with higher compliance (mean delivered PEEP increased by 0.8 and 0.6 cmH 2 O, respectively).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We did not record the respiratory system compliance in this experiment but expect it was within the range of 0.2–0.3 mL/kg/cmH 2 O, as shown previously 39. Compliance affects PEEP delivery: Tracy et al 18 tested 0.5 and 3 mL/cmH 2 O, and Thallinger et al 21 tested 0.1–0.2 and 0.8 mL/cmH 2 O. At a set PEEP of 5 cmH 2 O, both studies showed better PEEP provision with higher compliance (mean delivered PEEP increased by 0.8 and 0.6 cmH 2 O, respectively).…”
Section: Discussionmentioning
confidence: 54%
“…The paired models that perform closest to these requirements are Ambu and Mayo Healthcare, which provide more reliable mean PEEP in the absence of leak, according to this and previous17 18 studies. The Laerdal Upright Resuscitator has the advantage of an inbuilt PEEP valve and also provides less PEEP decay21; however, only fixed levels of PEEP (5 or 10 cmH 2 O) can be set, and its availability at the time of our study was restricted 38…”
Section: Discussionmentioning
confidence: 99%
“…The first study assessed the performance of the devices analysing videos of participants ventilating a manikin using an upright device compared to the standard device (33) . The second trial found that the vertical device offered higher volumes and lower mask leakage compared to the standard in a manikin model (34) . The third study developed a trial in Tanzania to compare both devices, and it founds relevant results favouring the upright device (35) .…”
Section: Discussionmentioning
confidence: 99%
“…We have not found studies evaluating prototypes similar to ours. However, in 2017, the results of the evaluation of the performance and acceptability of a self-inflating neonatal bag for vertical use were published compared to the conventional design for use in the standard transverse position (33)(34)(35) . The first study assessed the performance of the devices analysing videos of participants ventilating a manikin using an upright device compared to the standard device (33) .…”
Section: Discussionmentioning
confidence: 99%
“…We used binary regression with log-link function to estimate relative risks for ENM by time [13,15]. Risk factors which changed over time and were associated with the outcome (p<0.10) were included in a multivariate regression model if they changed the relative risk estimates by >10%.…”
Section: Methodsmentioning
confidence: 99%